2016
DOI: 10.1111/jppi.12155
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Physical Fitness Field‐Based Tests in Down Syndrome: A Systematic Review

Abstract: Physical fitness is an important marker of health that can be measured by means of field‐based tests, though research about its psychometric properties when performed by people with Down syndrome is scarce. A systematic review was designed to identify the validity and reliability of the existing physical fitness field‐based tests that have been administered to individuals with Down syndrome. An evidence‐based search for peer‐reviewed studies was conducted informing about the reliability and/or validity of phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
(92 reference statements)
0
7
0
1
Order By: Relevance
“…In the scientific literature, there exists research with the aim to determine the PF level of people with DS. According to the systematic review carried out by Ayán et al [10], most of them have been centred on performing a series of tests and describing the PF data obtained without previously checking the reliability and feasibility of the tools used in this population. In other cases, the test–retest has been analysed in one or various isolated tests—the majority obtained from a specific physical capacity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the scientific literature, there exists research with the aim to determine the PF level of people with DS. According to the systematic review carried out by Ayán et al [10], most of them have been centred on performing a series of tests and describing the PF data obtained without previously checking the reliability and feasibility of the tools used in this population. In other cases, the test–retest has been analysed in one or various isolated tests—the majority obtained from a specific physical capacity.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to psychometric properties, it has been highly recommended to emphasise providing information on measurement error as it contributes additional information to the ICC [41]. In a bibliographic review on PF tests in people with DS [10], it was concluded that although there exists much research, the tests on feasibility and reliability are scarce and are mainly performed in groups of young people. In this work, we also present MDC values which supplement those obtained in the ICC, SEM and feasibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it has been demonstrated that individuals in this group present with worse muscle strength than subjects with no disabilities [ 8 ]; therefore, many individuals with intellectual disability have behaviors and lifestyles that involve significantly lower levels of physical activity. Sedentary lifestyle and lack of sufficient exercise may in turn lead to foot deformation [ 9 , 10 ]; therefore, it is important to determine whether the above factors affect foot shape, leading to flat foot deformity. There are few reports on foot shape of individuals with intellectual disability.…”
Section: Introductionmentioning
confidence: 99%